ANALYSIS OF WAREHOUSE PERFORMANCE AUDITS TO IMPROVE COMPANY COMPETITIVENESS - Hartati, Verani; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
The increasing competition requires companies to improve their logistics performance. One of the important components in logistic performance is warehouse performance. The effort to improve warehouse performance competency is to conduct a comprehensive audit process on the role and performance of the warehouse, which aims to obtain an actual portrait of the warehouse capability. The warehouse check-up method is a method of auditing processes from seven perspectives: strategy, process, operations, costs, facilities (infrastructure), information systems, and people (human resources). The case study of the audit process in this research was conducted at the PT SCN warehouse, which is a distributor of fashion products in Indonesia. The scope of the audit includes the unloading of goods in the receiving, putting away, storing, picking, sorting, and loading activities in the shipping area. The results obtained indicate that the PT SCN warehouse got a final score of 71.25. The score indicates that the company’s warehouse is in the status of needing improvement. This paper suggests some improvement efforts that should be carried out by warehouse management. Improvements are focused primarily on the perspective of processes, operations, and people